Perancangan Aplikasi Rekapitulasi Stok Menggunakan Metode Prototype ( Studi Kasus Pada RCJ CELL Boyolali ) - Raka Angger Pamungkas; Donna Setiawati; Wisnu Sanjaya (JITU : Journal Informatic Technology And Communication, 2021)
The development of information technology today has grown very rapidly. One application of information and communication technology used is the development of a stock recapitulation system. The recapitulation of inventory records is very important for business actors. The stock of goods that are always available is an added value for buyers who are never disappointed when they run out of stock when they want to buy. This study aims to build a stock recapitulation system for warehouses and branches. The method used in this research is a prototype. The results of this study are a stock recapitulation system that can see the stock of warehouse and branch items in a timely manner and there is a direct notification feature to the owner when there is a little stock left.